Ownership Structure and Company Growth on Company Value: Intervened By Profitability - Ashara, Rega Aprilia; Lusiana, Lusiana; Sari, Desi Permata (GOVERNORS, 2024)
This research aims to determine the influence of Ownership Structure and Growth on Company Value with Profitability as an intervening variable in Manufacturing Companies in the Food and Beverage sub-sector listed on the Indonesia Stock Exchange (BEI) for the 2019-2023 period. Sampling in this research using the purpose sampling method obtained 35 companies with time series data. The analytical method used in this research is multiple linear regression analysis using SPSS 21. The research results show that partial ownership structure has no effect on profitability. Partial growth has no effect on profitability. Ownership structure partially influences company value. Partial growth has no effect on Company Value. Profitability partially influences company value. Ownership Structure and Growth simultaneously have no effect on Profitability. Ownership Structure, Growth and Profitability simultaneously influence Company Value.